Mapping Trends in Music Education Based on Solfeggio : A Bibliometric Study with Implications for Non-Music Vocational Students - Novianti, Dwi; Yulia, Cica; Sudiapermana, Elih; Rozak, Rama Wijaya Abdul (Jurnal Paedagogy, 2025)
This research aims to map the trends in international scientific publications related to solfeggio-based music education during the period 2016–2025 and to identify its implications for learning in non-music vocational high schools. The method used is a bibliometric study by analyzing data from the Scopus database using the keywords solfege, ear training, sight singing, sight reading, and music pedagogy. The data were analyzed using the VOSviewer tool to map trends, keyword clusters, and research focus. The results show that publications during the period 2021–2025 experienced a significant increase and formed three main clusters, namely music pedagogy and learning design, aural skills, and formal educational contexts such as conservatories. However, there is no focus on non-music vocational education contexts, indicating a research gap. These findings emphasize the need for the development of an inclusive, adaptive, and contextual solfeggio learning model, particularly for vocational high school students who do not have a formal music education background. This study provides an initial contribution in bridging the gap between formal music education studies and the need for musical learning in non-music vocational environments, as well as opening opportunities for the development of applied research in the future.